Empowering learning engagement in higher education with active learning experiences in STEM classrooms - Michael Angelo A. Legarde; Mercibelle Del Mundo; Jason V. Chavez; Ayessa Bahang Jailani; Kier P. Dela Calzada; Aldrin Rey C. Quisay; Kia P. Piñero-Abdurajak (Environment and Social Psychology, 2025)
Students often feel disengaged in class discussions due to ineffective teaching methods, such as passive lectures and over-reliance on learning materials, which lack interactive elements like group work or open discussions. Repetitive, simplistic content further diminishes interest by failing to challenge them. Uninspired teaching attitudes and outdated, irrelevant learning materials undermine motivation and fail to connect studies with real-world applications. This paper explored how active learning experiences in classrooms encourage students to participate in class activities and discussions. Fifteen science, technology, engineering and mathematics (STEM) college students were purposely sampled for this study. Their experiences in learning STEM-related subjects were explored through one-on-one interviews, allowing for the collection of detailed narratives. The findings revealed that several active learning strategies effectively engaged students in the learning process. The relevance of learning materials to real-world contexts significantly enhanced engagement, as students valued instructors who connected theoretical concepts to practical applications and current events. The flipped classroom approach also emerged as a powerful method, enabling students to transition from passive learning to active participation through discussions and hands-on activities during class presentations. Teachers’ energy and passion for the subject not only enlivened even challenging or monotonous material but also inspired students to engage more actively, which transforms the classroom dynamic into one of motivation and intellectual curiosity. Timely and constructive feedback was essential in maintaining student engagement, as it guided improvement, encouraged reflection, and supported a collaborative learning atmosphere. Rather than passively receiving information, students actively engage through activities such as discussions, problem-solving, hands-on tasks, and group projects.